IMPLEMENTASI APLIKASI PERENCANAAN KEUANGAN KELUARGA BERBASIS MOBILE - Andi Yulia Muniar (Celebes Computer Science Journal, 2020)
Family Financial Planning Application is very petrified in managing and maintaining financial stability, this application was developed by utilizing a wallet inspection simulation, budget and financial goal simulation embedded in an android-based application program. BlackBox test results by testing the features and actions stating that the account maker was successfully done, selecting the account successfully selected, input cash flow out and enter successfully, using the financial calculator according to the equation, use the calculation results as the account was successfully worked.